INNV-18. PROLONGED REMISSION AFTER TREATMENT WITH SINGLE-AGENT IBRUTINIB AS MAINTENANCE THERAPY FOLLOWING SALVAGE RADIATION THERAPY FOR REFRACTORY/RELAPSE PRIMARY CNS LYMPHOMA. (14th November 2022) - Du, Steven; Bota, Daniela; Kong, Xiao-Tang
Abstract: INTRODUCTION: Primary central nervous system lymphoma (PCNSL) is a rare and aggressive disease. Standard induction therapy for PCNSL consists of a high-dose methotrexate-based (HD-MTX) regimen. For relapsed or refractory primary CNS lymphoma (r/r PCNSL), most of the non-standard treatment regimens including additional chemotherapy, stem cell transplant, or whole brain radiation therapy (WBRT) may not reach long-term remission due to intolerance of the treatment by the patients or lack of effects. Here we report a case with r/r PCNSL reached more than 50-month remission after salvage WBRT followed by single agent ibrutinib maintenance therapy. CASE REPORT: a 75-year-old female with PCNSL, experienced disease recurrence, despite undergoing multiple lines of treatment including initial HD-MTX, second-line rituximab and temozolomide, repeated HD-MTX, and a clinical trial. Because her disease was refractory to these treatment options, we decided to start WBRT as salvage therapy, which resulted in significant reduction of tumor burden. Prior studies, however, showed that r/r PCNSL patients who underwent salvage WBRT alone had a median survival of only 1-2 years. Therefore, to extend the remission after salvage WBRT, she opted to try ibrutinib, a Bruton's tyrosine kinase inhibitor with past success in treating r/r PCNSL patients, as maintenance therapy after salvage WBRT. She tolerated well and decided to be off the treatment after 18 month-maintenance therapy. The patient has been stable clinically. She has since survived for more than 50 months after the completion of salvage WBRT plus maintenance therapy with ibrutinib. DISCUSSION: Compared to prior reports of 11 to 16 months of median survival after salvage WBRT alone for r/r PCNSL, our case has had prolonged survival, which supports the potential positive effect of ibrutinib as maintenance therapy for r/r PCNSL after salvage WBRT